Geosynthetic reinforced soil retaining walls with cohesive backfills - Franco, Yara Barbosa (2023)
Where granular materials are not easily available, local cohesive soils are increasingly employed in geosynthetic reinforced soil walls as a cheap and sustainable option. Conventional design methods do not yet account for the beneficial effect of cohesion in reducing the amount of required reinforcement. Similarly, the contribution of the face to stability is rarely accounted for, despite plenty of experimental evidence in its favour. This thesis evaluated the influence of soil cohesion and a structural facing on the stability of reinforced soil walls by using two approaches: the first was a semi-analytical approach while the second one an experimental approach.  The semi-analytical method employed is based on limit analysis for the design of reinforced soil walls in frictional-cohesive backfills accounting for the wall contribution. A parametric analysis was conducted to evaluate the effect of soil cohesion and friction angle, facing batter, block width, location of the reaction force acting on the face, facing backfill interface friction, facing-foundation interface friction and reinforcement length. Dimensionless design charts providing the required amount of reinforcement for lengths recommended in design standards are provided for both uniform and linearly increasing reinforcement distributions. It emerges that accounting for the presence of cohesion and the facing element can lead to significant savings in the overall level of reinforcement, and that tension cracks can be particularly detrimental to wall stability for highly cohesive soils so they cannot be overlooked in the design.  The second part of the study comprised the construction, testing and analysis of a 1.47 m high reinforced soil wall model, constructed with a frictional-cohesive soil and a modular block wall facing at LabGsy Laboratory, in São Carlos-SP, Brazil. The model wall was constructed using a dry-stacked column of masonry concrete blocks with a fully restrained toe, with an intended eight-degree facing batter. The backfill soil used was a cohesive-frictional backfill, classified as a sandy-clay. The reinforcement material comprised of 5 layers of relatively weak polyester (PET) knitted geogrid, modified to reduce its stiffness by cutting out some longitudinal ribs. Once constructed the wall was incrementally surcharged to maximum pressure of 150 kPa, limited by airbag capacity. The wall was heavily instrumented to monitor displacements at the facing, surface soil settlements, foundation earth pressures, vertical and horizontal toe loads, and displacements and strains in the soil reinforcement layers.  It was presented the materials, methods, instrumentation design and construction and test box adaptations needed to surcharging the wall model up to 150 kPa. The small magnitude of wall facing deflections measured during construction and surcharging seems to indicate the the model wall was possibility under working stress conditions throughout the entire physical test, far from reaching failure. This could be attributed to the overconsolidated state of the backfill soil due to compaction effort, to the beneficial effect of cohesion on reinforced soil wall behaviour and to the influence of the restrained wall toe to carry part of the load. This indicates that reinforced soil walls built with cohesive soil can perform well since its drainage can be guaranteed. It is expected that the contributions regarding the studies proposed herein can be a step forward in the understanding of the behaviour of GRS-RW with cohesive soils.  Finally, it was developed a series of python scripts to conduct automated numerical analysis in Plaxis 2D by using remote scripting, with the intention of laying the basis for a future numerical study involving automated parametric analysis of reinforced soil walls.